Improvement of physical qualities during sensitive periods in middle-distance track and field athletes - Sorokin, D.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to provide theoretical and experimental justification for an integrated training method for middle-distance runners aged 14–17, which involves a rational combination of volume-aerobic and interval-speed training methods in the structure of mesocycles, taking into account sensitive periods of physical development. Methods and structure of the study. 28 students from the Russian State Agrarian University - Moscow Timiryazev Agricultural Academy who were involved in athletics took part in the experiment. In the first, volume-aerobic system, the weekly training volume was 35–40 km at an intensity of 65–75% of the maximum heart rate (HR), and in the second system, it was 20–25 km with intervals at 85–90% of the maximum HR. Results and conclusions. The use of volume-aerobic methods ensures more stable development of endurance and functional indicators of the body, while the interval-speed approach contributes to accelerated growth of speed-strength abilities and improved coordination. The first system builds a solid aerobic foundation and improves the economy of movement, while the second stimulates neuromuscular responses and develops the ability to quickly change running pace. The most pronounced training effect is achieved by combining both methods, which ensures the harmonious development of both endurance and speed.